Indian economic thought : a preface to its history - Spengler, Joseph J. (Durham, N.C. : Duke University Press, 1971)
The purpose of this study is to survey the course of Indian economic thought and to stimulate intensive, organized inquiry.
Includes index.
Includes bibliographical references: p. 163-181.
rpm 07/11/2017
Loans
Keywords: Economics